Influence of Organic Manures and Foliar Sprays on Soil Microbial Population, Crop Growth and Seed Yield of Green gram - ASHOK S SAJJAN (Seed Research, 2026)
The influence of organic manures on soil beneficial micro-organisms, crop growth and seed yield parameters of Green gram (Vigna radiata) were studied. The population load of fungi, bacteria and actinomycetes was affected significantly with different rates of organic manures at all the stages of crop growth. Increasing trend of soil microbial population viz., bacteria, fungi and actinomycetes was noticed at 50% flowering and further it declined at harvesting stage and higher crop growth parameters of plant height (66.33 cm), number of trifoliate leaves (6.87), dry matter accumulation (11.15 g/plant) and higher yield attributing parameters like number of pods per plant (21.27), pod length (10.25 cm), number of seeds per pod (12.10) and seed yield per hectare (1263 kg/ha) was obtained in treatment combination of FYM 1/3+VC 1/3+GLM 1/3+ foliar spray of 3% panchagavya.